أثر الإمداد الكهربائي في جذب وتشجيع الاستثمار الأجنبي المباشر للسودان: نموذج قياسي للفترة من (2011-2020)م - د. أيمن عبد الغني حمزة العوض (White Nile Journal for Studies and Research, 2023)
The study dealt with the impact of electricity power supply in attracting and encouraging foreign direct investment to Sudan for the period from (2011-2020). The problem of the study was the weak production of electricity and the instability of the electric supply, which in turn negatively affects the in flow of foreign direct investment to Sudan, and the study assumed that there is a significant relationship A statistic between electricity production and the flow of foreign direct investment to Sudan, and the study followed the integrated descriptive and analytical approach, and the most important results were that there is direct statistically significant relationship between electricity production and the flow of foreign direct investment to Sudan, and that an increase in electricity production by one unit leads to an increase in the volume of electricity flow Foreign direct investment by (0.126), with an explanatory power of the model amounted to (R2 =0.83), and the most important recommendations It is necessary to develop strategic plans for the advancement of the electricity sector and its economies, taking into account the continuous expansion of the various consumers sectors in order to achieve stability and to cover the volume of demand to attract and encourage foreign direct investment. Keywords: electricity, foreign direct investment, attraction, encouragement.